Status of physical development of teenagers from 11 to 12 years of basic medical group during the school year - Таможанська Ганна Валеріївна, (Ganna Tamozhanskaya) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to define the changes age of anthropometric indexes of girls and boys from 11 to 12 years of basic medical group. Material and Methods: pedagogical research (somatometry and somatoskopia) of teenagers is conducted from 11 to 12 years (girls 79; boys 91) of basic medical group of Kharkov general schools. Results: the features of physical development of teenagers are Set from 11 to 12 years of basic medical group at the beginning and at the end of school year. The amount of teenagers is determined with the basic type of carriage, flat and planoconcave, round and stoop back. Conclusions: the state of morphological indexes of teenagers is certain from 11 to 12 years of basic medical group. The changes of types of carriages are educed for girls and boys of basic medical group for a school year.